Pengembangan Ide Bisnis Startup Little Farm: Digital Farming Solution Dengan Penerapan Metode Lean Startup - Suhandi, Nazori; Sunardi, Hastha; Kanaka, Nayaka Al Syahreal (UNIVERSITAS INDO GLOBAL MANDIRI, 2023)
The Sustainable Development Goals or SDGs are documents containing 17 goals and 169 targets that are valid from 2016 to 2030. Indonesia is one of the countries that attended the general assembly, agreed to the document, and is active in achieving the goals that have been ratified. Of the 17 goals in the SDGs, goal 2 contains eliminating hunger, achieving food security and nutrition, and promoting sustainable agriculture. One way to do this is by gardening, but some people in urban and suburban areas have limited land. The problem of limited land can be overcome by the hydroponic method which uses water as a planting medium. There have been several similar systems that have been developed, but only focus on the monitoring and control functions of hydroponics. Little Farm as a startup developing applications and systems based on the Internet of Things will help people to manage their hydroponics more easily, and can become a new source of income to increase their economic level. The application will be developed using the lean startup method which has 3 flows, namely build, measure, and learn. The process begins with making observations on the Google search engine. Then the observation results become a reference in developing Little Farm. The final form of this research is the Little Farm application prototype. Applications will continue to be developed based on user research and feedback.